(untitled) (Estudos em Design, 2024)
In this essay we carry out a critical and deconstructive analysis of the dualist foundation established by Horst Rittel and Melvin Webber in their 1973 paper “Dilemmas in a general theory of planning”. The aim is to escape the aporia launched by the two authors, when they ontologically distinguished scientific and engineering fields from planning and public policy fields, by establishing the concepts of “Wicked Problems” and “Tame Problems”. In order to propose an alternative, monist description, we sought theoretical reference in the same reasoning as Rittel and Webber for their dualist thesis: in Karl Popper’s epistemological demarcation between science and metaphysics, and in Thomas Kuhn’s metaphor of science as puzzle-solving.